Validation of Micro-Slip in Interference Fitted Shafts Subject to Complex Loading Regimes - McMillan, Martin; Smith, David John; Booker, Julian D. (Applied Mechanics and Materials, 2011)
The intention of the present work reported is to provide a detailed characterisation of the factors that contribute to failure of interference fitted joints under combined axial and torsional loading conditions and to provide analytical and finite element based simulations of the slip propagation and interfacial stresses leading to a failure envelope indicating the limits of each loading component in service to avoid premature failure. Small scale tests are conducted to examine failure torque and failure load separately before combined loading regimes are applied. The experimental tests are used to validate each stage of model development and the key parameters such as interference are measured under test conditions for use in the simulation models. The measured probabilistic variation in manufactured specimens will allow parametric studies to be carried out using finite element analysis and ultimately, provide a more comprehensive, validated approach for interference fit design.